Four Metaphors of Modernism : From Der Sturm to the Société Anonyme - Anger, Jenny, 1965- (Book collections on Project MUSE., 2018)
"Herwath Walden's Der Sturm--the journal, gallery, performance venue, press, theater, bookstore, and art school in Berlin (1910-1932)--has never before been the subject of a book-length study in English. In Four Metaphors of Modernism, Jenny Anger positions Der Sturm at the center of the avant-garde and as an integral part of Euro-American modern art, theory, and practice"--